Dissolution Modeling of Bead Formulations and Predictions of Bioequivalence for a Highly Soluble, Highly Permeable Drug - Sperry, David C; Thomas, Steven J; Lobo, Evelyn (Molecular pharmaceutics, 2010)
The objective of this study was to assess the impact of observed in vitro dissolution rate differences on in vivo pharmacokinetics for two enteric-coated bead formulations of a highly soluble, highly permeable drug. A new bead dissolution model was developed to quantitatively simulate the dissolution profiles of the two formulations. The model is based on the boundary layer diffusion model and can be used to simulate dissolution profiles for bead formulations using physicochemical properties of the formulation. The model was applied to show that the observed differences in dissolution profiles can be attributed completely to the difference in surface area of the beads for the two formulations. An absorption/pharmacokinetic model (GastroPlus) was used to predict the in vivo plasma concentration time profiles for the formulations using their respective in vitro dissolution profiles as input. The simulation results showed that the plasma concentration−time profiles were not significantly impacted by slower dissolution rates. Additionally, a sensitivity analysis was performed with a range of dissolution rate profiles. The fastest dissolution rate reached 80% dissolved in 41 min, while the slowest reached 80% in 114 min. Over this range, the predicted C max decreased by 9% and the AUC decreased by 1%. An in vivo bioequivalence study on the two experimental formulations demonstrated the formulations were bioequivalent, consistent with predictions. The lack of sensitivity is attributable to the high permeability and long elimination half-life of the drug. The work presented in this article demonstrates the use of a bead dissolution model and an absorption/PK model to predict in vivo formulation performance.